Floral UV Features of Plant Species From a Neotropical Savanna - Tunes, Priscila; Camargo, Maria Gabriela Gutierrez; Guimarães, Elza (Frontiers in Plant Science, 2021)
Despite the wide interest in flower colours, only after the end of the nineteenth-century studies started to comprise floral UV reflection, which is invisible to humans but visible to the major groups of pollinators. Many flowers and inflorescences display colour patterns, an important signal for pollinators, promoted by the presence of at least two different colours within flowers or inflorescences, including colours in the UV waveband. For Neotropical savanna plant species, we characterized floral UV features using UV-photography and reflectance measurements. We tested (i) whether floral UV features were constrained by their shared ancestry, (ii) whether floral UV features were associated with pollinators, and (iii) whether floral UV features were associated with floral traits mediating these interactions, including floral resource, type of attraction unit and presence/ absence of non-UV colour patterns. Of 80 plant species, ca. 70% were UV-patternless, most of them UV-absorbing. Approximately 30% presented one of three types of UV-patterns: bullseye, contrasting corolla markings oriented towards floral resources or contrasting reproductive structures, which were all considered as floral guides. Floral UV features were phylogenetically constrained and were associated with pollinators, floral resources and attraction unit, but not with non-UV colour patterns. UV-patternless flowers were associated with most of the pollination systems, while UV-patterned flowers were mainly associated with bee-pollination. UV-absorbing flowers comprised the only category with hawkmoth- and butterfly-pollinated flowers, and a high percentage of hummingbird-pollinated species. Nocturnal pollinated species were also commonly UV-absorbing, except for one UV-reflecting bat-pollinated species and one beetle-pollinated species with UV-reflecting stigmas. All types of floral UV features were associated with nectar; however, flowers with contrasting reproductive structures were mainly associated with pollen. There was an association between UV-absorbing species and the presence of inflorescences and intermediate attraction units. Our results evince that phylogenetic relatedness can constraint floral UV features’ diversification, but combinations of evolutionary and ecological processes may be expected in this scenario.